xdy/dx+y=1/y^2:using substitution in differential eq 1. The problem statement, all variables and given/known data solve using substitution xdy/dx+y=1/y^2 3. The attempt at a solution Thanks to the people who've help me thus far. here's a bernulli problem that I'm having. I change this problem around to... dy/dx=y^3/xy^2 xy^2dy=y^3dx using u sub. u=y^3 du=3y^2dy substituted problem 1/3xdu=udx du/dx=3xu du/dx-3xu=0 then I get e^(integral -3x)=e^(-3x^2/2) Here's where I'm stuck e^(-3x^2/2)u=integral 0*e^(-3x^2/2) doesn't that just have c? which later becomes u=ce^(3x^2/2) However, that's not the solution of the equation which is y^3=1+cx^-3 Can someone explain why?